Vulvar Lobular Capillary Hemangioma: A Rare Location for a Frequent Entity - F. Abreu-dos-Santos; S. Câmara; F. Reis; T. Freitas; H. Gaspar; M. Cordeiro (Case Reports in Obstetrics and Gynecology)
Lobular capillary hemangioma, or pyogenic granuloma, is an acquired hemorrhagic benign vascular lesion of the skin and mucous membranes. The pyogenic granuloma of the vulva is a rare finding and a limited number of case reports are available in the literature. To the best of our knowledge this is the first case described as a single pyogenic granuloma on the vulva.